Augustine and the Catechumenate - Harmless, William; Fitzgerald, Allan (Collegeville, MN : Liturgical Press, 2014)
As one of the most influential thinkers in Christian history, St. Augustine (354-430) had a flair for teaching and meditated deeply on the mysteries of the human heart. This study examines a little-known side of his career: his work as a teacher of candidates for baptism. ln the revised edition of this seminal book, both the text and notes have been revised to better reflect the state of contemporary scholarship on Augustine, liturgical studies, and the catechumenate, both ancient and modern. This edition also includes new findings from some of the recently discovered sermons of Augustine and incorporates new perspectives from recent research on early Christian biblical interpretation, debates on the Trinity, the evolution of the liturgy, and much more. This reconstruction of Augustine's catechumenate provides fresh perspectives on the day-to-day life of the early church and on the vibrancy and eloquence of Augustine the preacher and teacher.
Catechesis as a Performing ArtThe Well-Tempered Word; The Art of Persuasion; The Dark Side; The Visible Word: Liturgy; The Sermon as Catechesis; The Pedagogy of Silence; The Shape of Mystagogy; Catechesis as Liturgical Theology; The Written Word: The Scriptures; The Bread of the Word; Breaking Open the Bread of the Word; The Musicality of the Word; The Word-Made-Flesh: Christ; The Melody of Christ; Christ and Conversion; Select Bibliography.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072, 600
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.; Augustine, -- Saint, Bishop of Hippo; Catechumens -- Algeria -- Hippo (Extinct city) -- History; Hippo (Extinct city) -- Church history; Catechumens; Algeria -- Hippo (Extinct city); RELIGION / Christian Education / General; Electronic books; Church history; History